Analisis Riset Kalkulus Peubah Banyak Dengan Database Google Scholar Menggunakan VosViewer - Joko Soebagyo; Dzulhijjah Atdina Putri (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. This research is a bibliometric analysis conducted with the intention of studying publication trends, growth of citation patterns of authorship, identifying research collaborations, and others. The related aspects of individual journals, subject areas and institutions related to the theme of multivariable calculus. The researcher based their research on bibliometric analysis using data on journal articles with the theme of multivariable calculus on a database obtained from Google Scholar in the last 10 years. A total of 515 articles were obtained from the screening process. The results of the screening are realized in a mapping chart according to the year where the trend of research publications related to multivariable calculus is in the period 2012 to March 2022, where research related to multivariable calculus has a positive publication trend where 2021 is the year the most articles are published, and Taylor & Francis is a publisher. the most published articles related to multivariable calculus, where the article by V. Holten, C. E. Bertrand, M. A. Anisimov, and J. V. Sengers entitled “Thermodynamics of supercooled water” is the most cited article. Judging from the level of color density, in the density of visualization, the themes of function, case, study, teaching and derivatie are themes that are often studied, then themes that have dim colors such as fractional calculus, differential geometry, and graphs are themes that are still rarely studied.Abstrak. Penelitian ini merupakan analisis bibliometrik yang dilakukan dengan maksud sebagai studi tren publikasi, pertumbuhan kutipan pola kepengarangan, mengidentifikasi kolaborasi penelitian, dan lain-lain. Aspek-aspek terkait dari jurnal individu, bidang subjek dan institusi terkait tema kalkulus peubah banyak. Peneliti mendasarkan penetlitian pada analisis bibliometrik yang menggunakan data mengenai artikel jurnal yang bertemakana kalkulus peubah banyak pada basis data yang diperoleh dari Google Scholar dalam 10 tahun terakhir. Diperoleh sebanyak 515 artikel hasil dari proses penyaringan. Hasil dari penyaringan direalisasikan dalam grafik pemetaan sesuai tahun dimana tren publikasi riset terkait kalkulus peubah banyak pada rentang waktu 2012 hingga Maret 2022, dimana riset terkait kalkulus peubahbanyak mengalami tren publikasi yang positif dimana tahun 2021 menjadi tahun terbanyak artikel dipubikasikan, dan Taylor & Francis merupakan publisher yang paling banyak memublikasikan artikel berkaitan dengan kalkulus peubah banyak dimana artikel yang ditulis oleh V. Holten, C. E. Bertrand, M. A. Anisimov, and J. V. Sengersyang berjudul “Thermodynamics of supercooled water” merupakan artikel yang paling banyak dikutip. Dilihat dari tingkat kepekatan warna pada kerapatan visualisasinya, tema function, case, study, teaching dan derivatie merupakan tema yang sering diteliti, lalu tema yang memiliki warna yang redup seperti fractional calculus, differential geometry, dan graph merupakan tema yang masih jarang diteliti.